Inclusion emergency : diversity in architecture - Durham, Hannah; Choi, Grace (London : RIBA Publishing, 2024)
Architecture is at a tipping point. Voices of the under-recognised are increasing in volume and are agitating for change. If we don't collectively listen, re-adjust and change our outlook, we risk limiting the relevance of our profession in today's society and, ultimately, the places we create. Capturing insight from leading voices in the profession, this book encourages understanding and reflection. It addresses critical questions, providing steps towards meaningful change. It will help those who are under-recognised to find the role models, community and tools to feel confident, supported and valued. It will also help those intimidated by change to understand why it's so important and provoke constructive action. The topics and experiences provide a rich foundation for building an inclusive future that truly represents the diverse population we serve.
Keywords: Architecture -- Vocational guidance; Diversity in the workplace; ARCHITECTURE / Reference; ARCHITECTURE / General